Synthesis, Structural Characterization and Biological Screening of Manganese(II) Complexes Derived from Schiff Bases Containing Semicarbazone - VERMA, PARUL; SRIVASTAVA, PANKAJ (Asian Journal of Chemistry, 2010)
The synthesis and structural characterization of the complexes of Mn(II) is reported with general composition of [MnL1(H2O)2]Cl2 (L1 = Schiff bases ligands containing semicarbazone moiety). Complexes of manganese(II) with bis(furfuryl-2-aldehyde)semicarbazone (FALSCZ), bis(indole-3-aldehyde)semicarbazone (IALSCZ), bis(3-methylsalicylaldehyde) semicarbazone (MSALSCZ), bis(5-methylsalicylaldehyde)- semicarbazone (M'SALSCZ), bis(5-bromosalicylaldehyde) semicarbazone (BSALSCZ), bis(cinnamaldehyde)semicarbazone (CALSCZ), bis(4- chlorobenzaldehyde)semicarbazone (CHBALSCZ), bis(3,4,5,trimethoxy benzaldehyde) semicarbazone (TMBALSCZ), bis(pyridine-2-aldehyde) semicarbazone (PALSCZ) and bis(thiophene-2-aldehyde)semicarbazone (TPHALSCZ) have been synthesized and characterized by elemental analysis, molar conductivity, magnetic moments, thermal studies, EPR, IR and electronic spectra. The spectral data reveals that all the complexes show octahedral geometry around the metal ion. These complexes were also screened for their antibacterial and antifungal activities. The results reveal that the metal chelates are more potent than the parent ligands.